Dispersion and Attenuation of Elastic Wave Velocities: Impact of Microstructure Heterogeneity and Local Measurements. Issue 12 (30th November 2020) - Sun, Chao; Tang, Genyang; Fortin, Jérôme; Borgomano, Jan V. M.; Wang, Shangxu
Abstract: The variation of the seismic properties with frequency of a brine‐saturated sandstone sample with a porosity of 22% was measured using a forced oscillation apparatus. Two pairs of orthogonal biaxial strain gauges were pasted at different locations at the length center of the sample. In the frequency range of 1–300 Hz, using these two pairs of strain gauges, we observed experimentally the same global flow but different local flows (squirt flow). Therefore, the observation of the local flow is influenced by the position of the strain gauges in contrast to the global flow. Indeed, local flow is strongly influenced by the microstructure (structure of the grain contacts and microcracks). In particular, we show that although the sample is homogeneous in terms of porosity and crack density, it is not the case in terms of crack aspect ratio, which may slightly vary along the sample. A 3D diffusion model coupled with a simple squirt model was built to further interpret the data. These results show that the wave‐induced fluid flows occur at different scales and controls the dispersion and attenuation of saturated rocks. Key Points: Local and global flows can be sensed by strain gauge‐scale dispersion measurements The length center located strain‐gauge position mainly affects the attenuation related to squirt flow, but not that related to global flow Ultrasonic results are averaged properties and may not be used to predict in details the local dispersion measured by strain gauges